Social organization, culture and use of landscapes by livestock - Provenza F.D. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
The social facets of foraging typically are not considered in studies of food and habitat selection even though they are an indispensable part of the lives of most herbivorous mammals and of effectively managing landscapes. Through interactions with mother and peers, young animals learn what and what not to eat and where and where not to go in an environment, which collectively leads to the home-field advantage. The behavior of any individual is influenced as genes are expressed through interactions with social and biophysical environments, and experiences early in life markedly influence those relationships. Social organization leads to culture, wherein young animals learn from their ancestors through their mothers, and in the process the accumulated knowledge of how to use landscapes is passed from generation to generation. Cultures develop when learned practices contribute to the group's success in solving problems, and they evolve as individuals in groups discover new ways of behaving, as with finding new foods or habitats and better ways to use foods and habitats. Unfortunately, we have lost much of the knowledge of behavior used by our ancestors whose survival depended on hunting the wild herds and on domesticating ancestors of today's cattle, sheep, and goats. Our lack of appreciation of the social facets of foraging is apparent in the problems we encounter as we attempt to manage herbivores. Conversely, we can use knowledge of sociality to enhance management of landscapes to benefit soils, plants, herbivores, and people.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)